THE IMPLEMENTATION OF EMPLOYEE ENGAGEMENT FOR CADRE AND TEACHERS OF KULLIYATU-L-MU’ALLIMIN AL-ISLAMIYYAH IN DARUSSALAM GONTOR ISLAMIC BOARDING SCHOOL - Muhammad Kamalurrofiq; Fajar Surya Ari Anggara (University of Darussalam Gontor, 2021)
This research aims to find out and to analyze how the process of cadre recruitment at Darussalam Gontor Islamic Boarding School . The research also examines implementation of Employee Engagement for cadres and teachers at Darussalam Gontor Islamic Boarding School based on the factors of employee engagement initiated by Anitha J (2014). The research was using primary data that obtained from the interview process to carry out the teachers cadres and some stakeholders at the Darussalam Gontor Islamic Boarding School. While secondary data obtained from observation and documentation. This research uses triangular methods to analyze the data. The results of this study shows that the process of cadre recruitment at Darussalam Gontor Islamic Boarding School conducted over the five-term of Darussalam Gontor Islamic Boarding School. The Trimurti (three founders of Darussalam Gontor Islamic Boarding School) has been giving speeches to his successors to always perform the process of cadre recruitment for the sake of achieving goals and objectives of Darussalam Gontor Islamic Boarding School. The process of cadre recruitment at Darussalam Gontor Islamic Boarding School was well done and planned, it has a clear and structured process. Then, the existence of such cadre recruitment process Darussalam gontor Islamic Boarding School was always managed to produce qualified cadres in accordance with the resources needed by Darussalam Gontor Islamic Boarding School. Whereas, the implementation of the theory of Employee Engagement in the process of cadre recruitment at Darussalam Gontor Islamic Boarding School indeed leads to Employee Engagement factors initiated by Anitha J (GRG School of Management Studies, Coimbatore, India). However, those factors turned out to be not fully have an impact on individual cadres. There are other factors more influential. These factors are factors of spiritual as sincerity, guidance or instructions from Allah Subhanahu wa ta’ala, taufik or grace of Allah Subhanahu wata’ala, strengthening and accompaniment by Allah Subhanahu wa ta’ala, and God also Barokah (Blessed).